Politics, Pasteurization, and the Naturalizing Myth of Pure Milk in 1920s Saint John, New Brunswick - Jenkins, Jane (Acadiensis, 2008)
Abstract The controversy over milk pasteurization in Saint John during the 1925 New Brunswick election mirrored wider debates over the place of government in citizens’ lives as well as the role of science and technology in maintaining a viable dairy industry. Fought on these political and economic grounds, the debate centred on what constituted "natural" milk. While most farmers opposed pasteurization as too expensive, their acceptance of other technological and scientific alternatives to pasteurization, which focused on improving cow and barn hygiene, reveal that farmers did not oppose modernizing or progressive reforms.